PENINGKATAN KEMANDIRIAN ANAK USIA 4 – 5 TAHUN MELALUI METODE MENDONGENG DENGAN MEDIA BONEKA JARI DI TK PELANGI TENGGARONG SEBERANG TAHUN PELAJARAN 2016/2017 - Jumani Jumani; Mahkamah - Brantasari (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
This research aims to find out how to improve the independence of children aged 4-5 years through the method of storytelling with finger puppets in TK Pelangi Tenggarong Seberang in periode 2016/2017. This type of research using class action research methods (PTK) implemented in three cycles. The object of this research totalled 16. The data collection technique used was the observation that in the form of sheet of ebservations and documentation of the teacher and the student, while the results were analyzed using a quantitative descriptive method. The results of the analysis of the data indicates that an increase in cycle I became of 30.99% with. Cycle II increased to 58.86% with. Then in cycle III rose to 85.41% with appropriate expectations and growing category is growing very well. Conclusion on studies, that the application of the method of storytelling with finger puppets can increase self-sufficiency in children aged 4-5 years old in TK Pelangi about 77,60%.